FRASA NOMINA DIPRAMODIFIKASI FRASA ADJEKTIVA DALAM ARTIKEL GRAMMYS 2020: BIG SPEECHES AND EMOTIONAL MOMENTS - Lumanauw, Fiorentina Nispati Winona; Pakasi, Jenny H.; Ranuntu, Garryn Ch. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTÂ Â Â This research is about noun phrase pre-modified by adjective phrase. The aims of this research are to identify, classify the types of adjective phrase and to analyze the function of adjective phrase that appear before the head of noun phrase by using the theory of Aarts & Aarts (1982). The method used in this research is descriptive method. There are 70 noun phrases found in the five pages of â€œGrammys 2020: Big Speeches and Emotional Momentsâ€ article, within each noun phrases, there are 47 adjectives which function as pre-modifier. Those adjectives divided into seven types; adjective denoting nationality, adjective denoting substance, adjective denoting colour, adjective denoting age, adjective denoting shape, adjective denoting size, adjective denoting properties. Afterwards, noun phrases which contain adjectives have been analyzed by using a simple tree diagram. The results of the analysis show that each constituent has their own function as suitable as three functions in the structure of noun phrase: Determiner, Modifier and Head. Thereby, it has been proven that the function of adjective phrase is a pre-modifier of the head of noun phrase.Keywords : Syntax, Noun Phrase, Adjective Phrase, Pre-Modifier, Grammys 2020